Principal supervisors in Queensland: developing public school principal expertise at the nexus of hierarchy, markets and networks - Campbell-Allen, Ricky (2023)
Principal supervisors operate within the middle tier of schooling systems – connecting the policy-making centre with frontline leaders in schools. Existing research indicates that principal supervisors have been considered a promising lever for supporting and developing principals and implementing policy (Goldring et al., 2020). This research set out to understand how principal supervisors influence principal practice in the context of wider educational governance changes. Marketisation and New Public Management (NPM)-inspired reforms, including school autonomy, parental choice, and accountability policies, have been adopted in many school systems worldwide as policy makers have sought to improve educational performance and responsiveness. How such mechanisms play out in each place is distinct. This study employed governance theory (hierarchy, markets and networks) to examine the role of the principal supervisor, known as the Assistant Regional Director – School Performance (ARD), in the Queensland public school system. The ARD role has been introduced and evolved in the context of policy-driven efforts to raise academic test scores, enhance school autonomy and embed a new national curriculum in schools. Existing in most Australian public systems, the principal supervisor role (or equivalent) is typically focused on improving the principals' instructional leadership and includes responsibility for a group of schools. In Queensland, the region (middle tier) is a distinct geographically focused administrative tier embedded within the state-level education infrastructure – the Department, rendering it somewhat invisible. This study utilised a theory-led case study approach to inquiry with mixed methods (predominately qualitative) to present a cross-case analysis of three case studies of ARDs from three regions in Queensland. Data collection included a survey of ARDs (n=30) and semi-structured interviews (n=15) with ARDs, system leaders/informants and principals, and document and policy analysis. This study identified three overarching empirical findings. Firstly, the centre uses the ARD role as the primary capacity building steering mechanism to develop principal knowledge and expertise within the Queensland system. Secondly, ARD practice can be strengthened through regional coherence and collective sense-making processes – key aspects of the middle tier. Thirdly, the middle tier works to mediate and manage quasi-market, network and hierarchical pressures but struggles to ameliorate the negative effects of competition on equity. The findings add to our understanding of how the middle tier operates in a vertically integrated hierarchical context beyond the more widely studied tri-level district model. This study also makes a valuable theoretical contribution, as it has embedded a learning framework (how professional knowledge is developed and how this might relate to sources of expertise) within a governance analysis (hierarchy, markets and networks). At the most practical level, the findings from this study have implications for the selection, professional development and assigning of principal supervisors to schools. The findings have ramifications for equity and considerations of drivers of competition in local education markets, e.g., unregulated programs of excellence. More broadly, the study also has implications for how principal supervisor roles are designed and operate within wider meta-governance approaches to schooling that seek to balance the multiple aims of improvement, performance, equity, choice, the public good and value for investment.